2021
DOI: 10.1177/17085381211040984
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning prediction of diabetic foot ulcers in the inpatient population

Abstract: Background The objective of this study was to create an algorithm that could predict diabetic foot ulcer (DFU) incidence in the in-patient population. Materials and Methods The Nationwide Inpatient Sample datasets were examined from 2008 to 2014. The International Classification of Diseases 9th Edition Clinical Modification (ICD-9-CM) and the Agency for Healthcare Research and Quality comorbidity codes were used to assist in the data collection. Chi-square testing was conducted, using variables that positively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…With the continuous development of artificial intelligence, machine learning has been applied in the field of medical diagnosis and demonstrated better performance in the prediction of clinical disease prognosis [41]. In recent studies, many studies have shown the superior predictive power of machine learning algorithms for the diagnosis and prognosis of DFU [14][15][16][17][18][19]. However, there is a lack of studies with sufficient case data to determine comparatively which machine learning algorithm is the most suitable for use, especially in patients with UT3 DFU, which is most commonly seen in tertiary care hospitals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the continuous development of artificial intelligence, machine learning has been applied in the field of medical diagnosis and demonstrated better performance in the prediction of clinical disease prognosis [41]. In recent studies, many studies have shown the superior predictive power of machine learning algorithms for the diagnosis and prognosis of DFU [14][15][16][17][18][19]. However, there is a lack of studies with sufficient case data to determine comparatively which machine learning algorithm is the most suitable for use, especially in patients with UT3 DFU, which is most commonly seen in tertiary care hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…Machine learning plays an important role in the prediction of many common diseases, such as the diagnostic prediction of patients with type 2 diabetes [12] and the classification of cardiovascular diseases in patients with diabetes [13]. Several studies on DFU have shown the superior predictive performance of machine learning algorithms [14][15][16][17][18][19]. For the DFU diagnosis, Amith Khandakar et al used thermogram images to establish a machine learning model based on CNN for early detection of DFU [15].…”
Section: Introductionmentioning
confidence: 99%
“…In 2021, Stefanopoulos et al published a study based on a conditional inference tree (CTREE) algorithm for the prediction of DFU risk in an inpatient population [ 24 ]. Nationwide Inpatient Sample datasets (USA) from 2008 to 2014, including over 10 million diabetic patients (of which 326,853 had DFU), were used for model generation and testing.…”
Section: Artificial Intelligence In Diabetic Foot Syndrome: Methodolo...mentioning
confidence: 99%
“…41 Yap et al 42 created an app that allows users to determine whether an image contains a DFU, which is an especially useful tool for clinicians in regions where little training for DFU management exists or for use by vision-impaired patients. Stefanopoulos et al 62 used ML to retrospectively determine which patients in the Nationwide Inpatient Sample (a database which contains approximately 20% of all US hospital admissions) with active DFUs were noted to have a variety of risk factors. Using six risk factors incorporating both physical parameters and demographic information (cellulitis, Charcot joint, peripheral arterial disease, uncontrolled diabetes mellitus, peripheral vascular disease, and male gender), they developed an algorithm that can predict the likelihood of developing a DFU with 79.8% accuracy.…”
Section: The Use Of Ai To Diagnose Diabetic Foot Ulcersmentioning
confidence: 99%